A comparison between atmospheric/humidity and vacuum cyanoacrylate fuming of latent fingermarks. (December 2015) - Farrugia, Kevin J.; Fraser, Joanna; Friel, Lauren; Adams, Duncan; Attard-Montalto, Nicola; Deacon, Paul
Highlights: Atmospheric/humidity cyanoacrylate fuming is superior to the vacuum process. Atmospheric/humidity conditions are superior for both two-step and one-step process. A sequence of double treatments with Lumicyano yields a higher detection rate. Atmospheric/humidity fuming after vacuum fuming is possible. Vacuum cyanoacrylate fuming may have certain operational advantages. Abstract: A number of pseudo-operational trials were set up to compare the atmospheric/humidity and vacuum cyanoacrylate fuming processes on plastic carrier bags. The fuming processes were compared using two-step cyanoacrylate fuming with basic yellow 40 (BY40) staining and a one-step fluorescent cyanoacrylate fuming, Lumicyano 4%. Preliminary work using planted fingermarks and split depletions were performed to identify the optimum vacuum fuming conditions. The first pseudo-operational trial compared the different fuming conditions (atmospheric/humidity vs. vacuum) for the two-step process where an additional 50% more marks were detected with the atmospheric/humidity process. None of the marks by the vacuum process could be observed visually; however, a significant number of marks were detected by fluorescence after BY40 staining. The second trial repeated the same work in trial 1 using the one-step cyanoacrylate process, Lumicyano at a concentration of 4%. Trial 2 provided comparable results to trial 1 and all the items were then re-treated with Lumicyano 4% at atmospheric/humidity conditions before dyeing with BY40 to provide the sequences of process A (Lumicyano 4% atmospheric–Lumicyano 4% atmospheric–BY40) and process B (Lumicyano 4% vacuum–Lumicyano 4% atmospheric–BY40). The number of marks (visual and fluorescent) was counted after each treatment with a substantial increase in the number of detected marks in the second and third treatments of the process. The increased detection rate after the double Lumicyano process was unexpected and may have important implications. Trial 3 was performed to investigate whether the amount of cyanoacrylate and/or fuming time had an impact on the results observed in trial 2 whereas trial 4 assessed if the double process using conventional cyanoacrylate, rather than Lumicyano 4%, provided an increased detection rate. Trials 3 and 4 confirmed that doubling the amount of Lumicyano 4% cyanoacrylate and fuming time produced a lower detection rate than the double process with Lumicyano 4%. Furthermore, the double process with conventional cyanoacrylate did not provide any benefit. Scanning electron microscopy was also performed to investigate the morphology of the cyanoacrylate polymer under different conditions. The atmospheric/humidity process appears to be superior to the vacuum process for both the two-step and one-step cyanoacrylate fuming, although the two-step process performed better in comparison to the one-step process under vacuum conditions. Nonetheless, the use of vacuum cyanoacrylate fuming may have certain operational advantages and its use does not adversely affect subsequent cyanoacrylate fuming with atmospheric/humidity conditions.